IMPLEMENTATION OF PEER INSTRUCTION INTEGRATED GUIDED INQUIRY LEARNING TO INCREASE ARGUMENTATION SKILL OF SCIENCE JUNIOR HIGH SCHOOL STUDENTS - Nova Julianti; Azhar Azhar; Muhammad Nasir (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
This research aimed to know the differences in the science physics argumentation skills of students learning with the Peer Instruction Integrated Guided Inquiry Learning model and conventional learning. The research method used was quasy experiment with posttest only control design. The research population was all eighth grade students of Junior High School (SMP) 3 Pekanbaru. Samples were taken from two classes chosen by simple random sampling, namely class VIII5, totaling 36 students as the experimental class and class VIII4, totaling 36 students as the control class. The research instrument used a test argumentation skills. Data collection techniques through argumentation skills tests, after the learning process is carried out in both classes. Data were analyzed descriptively by looking at the results of students' argumentation skills scores and inferential using the T-test. The results of descriptive analysis showed that the experimental class argumentation skills were good enough, while the control class categorized was less good with a difference of 22.84%. Inferential there were significant differences in students' argumentation skills in class learning vibration and wave material with Peer Instruction Integrated Guided Inquiry Learning model to conventional class. The use of Peer Instruction Integrated Guided Inquiry Learning model in learning science of physics of vibration and wave material in class VIII5 of SMP 3 Pekanbaru, can increase the ability of students' argumentation skills.